2021
DOI: 10.1021/acsaem.1c00777
|View full text |Cite
|
Sign up to set email alerts
|

Polyacrylamide Gel-Derived Nitrogen-Doped Carbon Foam Yields High Performance in Supercapacitor Electrodes

Abstract: Porous carbons play a vital role in supercapacitor electrodes. The capacitive performance of porous carbons depends mostly on the pore structure and surface chemistry. It is highly desirable to develop robust methods to prepare porous carbons with controlled structures and compositions. Herein, a nitrogendoped carbon foam was prepared on the basis of polyacrylamide gel with K 2 CO 3 and K 2 B 4 O 7 as the activating agent and salt template, respectively. Due to the constraint effect of the cross-linked polyacr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 71 publications
0
14
0
Order By: Relevance
“…Besides the designed structure, the heteroatom doping and/or surface functionalization of porous carbon materials have also been recognized as promising methods to enhance their capacitive performance. The electronic structure, electronegativity, and atomic size of heteroatoms are obviously distinguished from those of host carbon atoms, which not only bring in high energy defect sites on the porous carbon framework but also adjust the electron donor–acceptor features for these heteroatoms. Therefore, the introduction of heteroatoms including B, N, P, O, and S into carbon frameworks has been deemed to be an attractive strategy for optimizing the porous carbon electrodes by increasing the electronic conductivity and enhancing the surface wettability. Moreover, distinct from single heteroatom dopants for carbon framework modification, multi-heteroatom dopants can carry more high-energy defect sites, which is more effective for activating the inert carbon framework due to the so-called synergistic effect. , Over the past decades, there have been many reports concerning the codoped (such as N/S, N/O, N/F, N/B, and N/P, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Besides the designed structure, the heteroatom doping and/or surface functionalization of porous carbon materials have also been recognized as promising methods to enhance their capacitive performance. The electronic structure, electronegativity, and atomic size of heteroatoms are obviously distinguished from those of host carbon atoms, which not only bring in high energy defect sites on the porous carbon framework but also adjust the electron donor–acceptor features for these heteroatoms. Therefore, the introduction of heteroatoms including B, N, P, O, and S into carbon frameworks has been deemed to be an attractive strategy for optimizing the porous carbon electrodes by increasing the electronic conductivity and enhancing the surface wettability. Moreover, distinct from single heteroatom dopants for carbon framework modification, multi-heteroatom dopants can carry more high-energy defect sites, which is more effective for activating the inert carbon framework due to the so-called synergistic effect. , Over the past decades, there have been many reports concerning the codoped (such as N/S, N/O, N/F, N/B, and N/P, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…In the low frequency region of the Nyquist plots, the curves of DAC-700 and DAC-800 were evidently steeper than that of DAC-600. This phenomenon indicated that the hierarchical pore structure of DAC-700 and DAC-800 is conducive to the migration of ions in the electrode, which lead to a relatively lower Warburg diffusion resistance ( Z w ). ,, …”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon indicated that the hierarchical pore structure of DAC-700 and DAC-800 is conducive to the migration of ions in the electrode, which lead to a relatively lower Warburg diffusion resistance (Z w ). 17,34,35 The electrochemical properties of all DAC samples were studied by GCD test. As displayed in Figure 6B, compared with DAC-600 (102.2 F/g) and DAC-800 (126.0 F/g), DAC-700 electrode showed the largest specific capacitance (263.9 F/g) when the current density was 1 A/g.…”
Section: Resultsmentioning
confidence: 99%
“…66,105,123–127 The in situ formed nanosized potassium bicarbonate, potassium carbonate and potassium oxide could serve as effective activation agents and templates for generating massive micro-/meso-pores, which greatly surpassed their counterparts derived from organic salts of Li, Na, Mg, Ca, Al, Zn, etc . 128–131 Moreover, the intermediate potassium species could be removed easily by water. 132 While the graphitic carbon layer encapsulating metal nanoparticles derived from organic salts of Fe, Co, Ni, Cu, etc ., are hard to completely removed, even upon treatment with strong acids.…”
Section: Introductionmentioning
confidence: 99%